Pilot Study on the Detection of Simulated Lesions Using a 2D and 3D Digital Full-Field Mammography System with a Newly Developed High Resolution Detector Based on Two Shifts of a-Se - Schulz-Wendtland, R. (Georg Thieme Verlag KG, 2012)
Purpose: Experimental study of a new system for digital 2D and 3D full-field mammography (FFDM) using a high resolution detector based on two shifts of a-Se. Material and Methods: Images were acquired using the new FFDM system Amulet® (FujiFilm, Tokio, Japan), an a-Se detector (receptor 24 × 30 cm(2), pixel size 50 µm, memory depth 12 bit, spatial resolution 10 lp/mm, DQE > 0.50). Integrated in the detector is a new method for data transfer, based on optical switch technology. The object of investigation was the Wisconsin Mammographic Random Phantom, Model 152A (Radiation Measurement Inc., Middleton, WI, USA) and the same parameters and exposure data (Tungsten, 100 mAs, 30 kV) were consistently used. We acquired 3 different pairs of images in the c-c and ml planes (2D) and in the c-c and c-c planes with an angle of 4 degrees (3D). Five radiologists experienced in mammography (experience ranging from 3 months to more than 5 years) analyzed the images (monitoring) which had been randomly encoded (random generator) with regard to the recognition of details such as specks of aluminum oxide (200–740 µm), nylon fibers (0.4–1.6 mm) and round lesions/masses (diameters 5–14 mm), using special linear glasses for 3D visualization, and compared the results. Results: A total of 225 correct positive decisions could be detected: we found 222 (98.7 %) correct positive results for 2D and 3D visualization in each case. Conclusion: The results of this phantom study showed the same detection rates for both 2D and 3D imaging using full field digital mammography. Our results must be confirmed in further clinical trials.